AN IMPROVED METHOD OF MANUFACTURING A COMPLETE REMOVABLE PLATE PROSTHESIS UNDER THE CONDITION OF INTOLERANCE TO ACRYLIC PLASTIC IN PATIENTS - Xojimurodov Burxon Ravshanovich (American Journals, 2023)
An original solution for the removal of completely missing teeth with intolerance to acrylic prostheses is presented. A reinforced full removable prosthesis made of polypropylene has been developed. Clinical trials have shown the advantages of the proposed method in comparison with the most common similar products.
Keywords: full removable prosthesis, polypropylene, intolerance to acrylic resin.